Locked Out: Ignorance and Responsibility in Brain–Computer Interface Communication in Locked-in Syndrome - Johansson, Veronica (Cambridge quarterly of healthcare ethics, 2017)
Brain–computer interfaces (BCIs) can enable communication for persons in severe paralysis including locked-in syndrome (LIS); that is, being unable to move or speak while aware. In cases of complete loss of muscle control, termed “complete locked-in syndrome,” a BCI may be the only viable solution to restore communication. However, a widespread ignorance regarding quality of life in LIS, current BCIs, and their potential as an assistive technology for persons in LIS, needlessly causes a harmful situation for this cohort. In addition to their medical condition, these persons also face social barriers often perceived as more impairing than their physical condition. Through social exclusion, stigmatization, and frequently being underestimated in their abilities, these persons are being locked out in addition to being locked-in. In this article, we (1) show how persons in LIS are being locked out, including how key issues addressed in the existing literature on ethics, LIS, and BCIs for communication, such as autonomy, quality of life, and advance directives, may reinforce these confinements; (2) show how these practices violate the United Nations Convention on the Rights of Persons with Disabilities, and suggest that we have a moral responsibility to prevent and stop this exclusion; and (3) discuss the role of BCIs for communication as one means to this end and suggest that a novel approach to BCI research is necessary to acknowledge the moral responsibility toward the end users and avoid violating the human rights of persons in LIS.